The Effect of Lavender Aromatherapy Relaxation Techniques on Labor Progress During Stage I Active Phase - Nurqalbi Sampara; Sumarni Marwang; Jumrah Sudirman; Mika Dwina Shafira (GLOBAL HEALTH SCIENCE GROUP, 2024)
The purpose of this study was to determine the effect of lavender aromatherapy relaxation techniques on the progress of active phase I labor at the Kassi-Kassi Public Health Center in Makassar. The design of this study was non randomized control group post test design. The number of samples was 30 women giving birth at the Kassi-Kassi Makassar Public Health Center. In sampling the technique used is non random technique with a purposive sampling approach and for data collection using instruments in the form of SOPs and partographs. The data analysis technique used the Mann Withney test to analyze the effect of lavender aroma therapy relaxation techniques on the progress of labor in the active phase I using a significant level α = 0.05. The results of the Man Withney test on the effect of lavender aromatherapy relaxation techniques on the progress of labor in the first phase of active phase, obtained a value of p = 0.004. These results indicate that ρ <α (0.004 <0.05). The conclusion of this study is the influence of lavender aromatherapy relaxation techniques on the progress of active phase I labor at Kassi-Kassi Makassar Public Health Center in 2019.